C.A. Wickliffe et al., The Revised Statutes of Kentucky 671 (1852) - (:unkn) unknown (My University, 1852)
Art. 7,§ 1: No person, except a gunsmith on his own premises, shall shoot off a gun or pistol in a town. Any person offending herein shall be fined five dollars and costs, to be collected by the trustees, and applied to keeping the streets of the town in repair.
Keywords: DISCHARGE